A randomized comparison of modified subcutaneous "Z"‐stitch versus manual compression to achieve hemostasis after large caliber femoral venous sheath removal. Issue 1 (17th March 2017) - Pracon, Radoslaw; Bangalore, Sripal; Henzel, Jan; Cendrowska‐Demkow, Iwona; Pregowska‐Chwala, Barbara; Tarnowska, Agnieszka; Dzielinska, Zofia; Chmielak, Zbigniew; Witkowski, Adam; Demkow, Marcin
Abstract : Objectives: To compare subcutaneous "Z"‐stitch versus manual compression in attaining hemostasis after large bore femoral venous access, and to assess its impact on venous patency. Background: Structural interventions increasingly require large caliber venous access, for which convenient, safe, and effective method of postprocedural hemostasis is needed. "Z"‐stitch has been introduced for this purpose in some centers but systematic data on its performance is limited. Methods: This single center study randomized consecutive patients with femoral venous access sites requiring ≥10F sheaths to the "Z"‐stitch or manual compression for hemostasis in a 2:1 fashion. There were three co‐primary endpoints: time to hemostasis, time to ambulation, and a composite safety endpoint comprising vascular access site complications. Groin Doppler‐Duplex was performed with the stitch in place and after its removal. Results: 86 consecutive patients with 90 access sites were randomized. Mean age was 61.7 ± 19.1 years, 33.3% were men. Median sheath size was 14 F (range 10–22 F). Patients randomized to "Z"‐stitch achieved hemostasis quicker [<1 min vs. 12.0 (IQR 10.0–15.0) min, P  < 0.001] and ambulated sooner [7.0 (IQR 4.0–12.0) vs. 16.0 (IQR 11.8–20.3) hr post procedure, P  < 0.001] when compared with manual compression alone. The "Z"‐stitch reduced rates of access site complications (OR = 0.27, 95%CI 0.09–0.76, P  = 0.01). All imaged veins were patent before and after stitch removal. Conclusions: The "Z"‐stitch is a safe and effective method of achieving hemostasis after large bore femoral venous sheath removal and results in faster hemostasis, early patient ambulation and less access site complications, without compromising vein patency when compared with manual compression alone. © 2017 Wiley Periodicals, Inc.